Temporal procedures of mutual alignment and synchronization in collaborative meaning-making activities in a dance rehearsal - Krug, Maximilian (Frontiers in Communication, 2022)
Synchrony is a members' interactional solution for dealing with multiple relevant interactional tasks simultaneously when working on two or more separate, perceptual, and equally relevant projects, e. g., when dancing while pointing out a feature of the ongoing dance. This paper focuses on moments in which participants engage in joint meaning-making to identify, negotiate, and implement displayed multimodal gestalts of the choreography. Three temporal procedures of mutual alignment and synchronization were identified through a conversation analytical approach in combination with marker-less motion tracking movement analysis of a dance rehearsal: delays, accelerations, and accentuations. The analyses revealed that synchrony requires constant coordination in order to establish, maintain, and dissolve alignment between participants and their multimodal resources.